PELATIHAN PEMBUATAN INFUSED WATER DENGAN BAHAN DASAR REMPAH SEBAGAI PENINGKAT SISTEM IMUN - Herwin; Rusli; Nuryanti, Siska; Fitriana; Nurung, Ayyub Harly (JURNAL PENGABDIAN FARMASI DAN SAINS, 2023)
The corona virus pandemic (SARS-CoV-2) that causes COVID-19, which has entered Indonesia since early March, has not shown significant signs of ending. The Indonesian government continues to urge the public to always adopt a clean lifestyle, one of which is by consuming food or drinks that can boost the body's immune system. Infused water is mineral water that gets a mixture of various kinds of pieces of fresh fruit, vegetables, herbs or spices. This activity was carried out using the lecture method and direct discussions with the people of RT 07 RW 03, Sudiang Village, Makassar City, South Sulawesi. The target in this service is that participants can add knowledge about how to improve the immune system and the benefits of infused water as a way to boost the immune system and participants can find out about how to make infused water from spice-based ingredients.